A randomised controlled trial of cognitive aids for emergency airway equipment preparation in a Paediatric Emergency Department. Issue 1 (December 2016) - Long, Elliot; Fitzpatrick, Patrick; Cincotta, Domenic; Grindlay, Joanne; Barrett, Michael
Abstract Background Safety of emergency intubation may be improved by standardising equipment preparation; the efficacy of cognitive aids is unknown. Methods This randomised controlled trial compared no cognitive aid (control) with the use of a checklist or picture template for emergency airway equipment preparation in the Emergency Department of The Royal Children's Hospital, Melbourne. Results Sixty-three participants were recruited, 21 randomised to each group. Equal numbers of nursing, junior medical, and senior medical staff were included in each group. Compared to controls, the checklist or template group had significantly lower equipment omission rates (median 30 % IQR 20–40 % control, median 10 % IQR 5–10 % checklist, median 10 % IQR 5–20 % template;p  < 0.05). The combined omission rate and sizing error rate was lower using a checklist or template (median 35 % IQR 30–45 % control, median 15 % IQR 10–20 % checklist, median 15 % IQR 10–30 % template;p  < 0.05). The template group had less variation in equipment location compared to checklist or controls. There was no significant difference in preparation time in controls (mean 3 min 14 s sd 56 s) compared to checklist (mean 3 min 46 s sd 1 min 15 s) or template (mean 3 min 6 s sd 49 s;p  = 0.06). Discussion Template use reduces variation in airway equipment location during preparation foremergency intubation, with an equivalent reduction in equipment omission rate to the use of a checklist. The use of a template for equipment preparation and a checklist for team, patient, and monitoring preparation may provide the best combination of both cognitive aids. Conclusions The use of a cognitive aid for emergency airway equipment preparation reduces errors of omission. Template utilisation reduces variation in equipment location. Trial registration Australian and New Zealand Trials Registry (ACTRN12615000541505 ).